Polar pollution: protecting Antarctic marine ecosystems from microplastics - Elliott Lancaster; Zina Lancaster; Vihara Marasinghe (Ukrainian Antarctic Journal, 2025)
Plastic contamination in Antarctica is a major environmental concern that has received international attention in recent years. This review investigates the factors that affect polar plastics, including their distribution, accumulation, socioeconomic effects, stakeholder alignments, ways to reduce plastic pollution, and policies that affect plastic pollution in Antarctica. The problem of plastic pollution is extremely important for the preservation of the environment in the Antarctic and on the planet. The spread of plastic pollution in Antarctica is mostly due to ocean currents transporting plastic debris from other parts of the world. The distribution of plastics is driven by human activities, which have led to severe environmental degradation. Now, climate change is exacerbating the problem, creating a destructive feedback loop. According to research, plastic waste is concentrated in specific parts of Antarctica, notably in ice-free areas. A solution to the escalating problem of plastic pollution lies in the development and adoption of sustainable policies and practices. By increasing environmental awareness around the harm microplastics impact on the environment, more advocates could address the importance of investing in innovative alternative materials, promoting circular economy principles for waste management, government intervention, and encouraging global stakeholder collaboration. By combining education, innovation, regulation, and community action, we can drive into a world where plastic accumulation is reduced and controlled, leading to a safe environment free of biological consequences in the Antarctic region. Through this, we can significantly change plastic consumption and save biodiversity. Furthermore, the engagement of scientific communities in long-term monitoring and the promotion of eco-friendly expeditions are vital to ensure progress. Strengthening international treaties can bolster the enforcement of regulations concerning plastic use and disposal. The collective efforts of individuals, institutions, and governments can have a significant impact, reversing the damage and setting a precedent for environmental protection worldwide.